Curauá fibers in the automobile industry - a sustainability assessment - Zah, R.; Hischier, R.; Leão, Alcides Lopes [UNESP]; Braun, I. (Elsevier, 2007)
Replacing glass fibers with natural fibers in the automobile industry can yield economic, environmental and social benefits. This article evaluates the prospective environmental impacts of automobile applications of curauá fiber (Ananas erectifolius), which nearly equates the physical properties of glass fibers. The study identified economic and social advantages of applying curauá fiber composites in car parts. Besides costing 50% less than fiber glass, the use of curauá fibers can promote regional development in the Amazon region. In order to realize significant environmental benefits, however, the curauá-based composites would have to be lighter than their glass fiber-based counterparts. © 2006 Elsevier Ltd. All rights reserved.
Keywords: Composites; Curauá; Life Cycle Assessment (LCA); Natural fibers; Passenger cars; Automobile manufacture; Environmental impact; Glass fibers; Life cycle; Social aspects; Sustainable development; Fiber-based counterparts; Sustainability assessment; Automotive industry; Ananas; Ananas comosus